PP.93 Pregnancy of Unknown Location Outcomes in an EPAU Setting. (26th April 2013) - Crosby, DA; Mullally, A; Farah, N; Anglim, M; Gul, S; Fitzpatrick, C
Abstract : Pregnancy of unknown location (PUL) refers to cases where there are no signs of intrauterine or extrauterine pregnancy on transvaginal ultrasound as well as no evidence of retained products of conception. The most recent report of the Confidential Enquiry into Maternal Deaths in the United Kingdom suggested that the term PUL should be abandoned and that "an early pregnancy ultrasound which fails to identify an intrauterine sac should stimulate active exclusion of tubal pregnancy". The Early Pregnancy Assessment Unit in the Coombe Women and Infants Maternity Hospital recorded 3, 900 patient visits during the study period. We examined cases of women with a diagnosis of PUL who presented between September 2011 and September 2012. Data was obtained retrospectively from routine information ascertained at the time of initial consultation and from patient records. 190 women had a diagnosis of PUL at their initial presentation to the EPAU. Mean gestation at presentation was 7.0 weeks (4.0–12.0). 158 women (83.1%) were subsequently diagnosed with complete miscarriage. 18 women (9.5%) had an ongoing intrauterine pregnancy. 14 women (7.4%) were diagnosed with an ectopic pregnancy at a subsequentvisit. The average number of samples taken for serum βhCG measurement was 2.3 and the average duration of follow-up of all women was 5.8 days. The incidence of PUL in women attending our unit was 4.8%. Conservative management of pregnancy of unknown location is safe when carried out in a setting which enables patients to be monitored closely with rapid access to transvaginal ultrasound and serum βhCG quantification.